The Role of Islam in Alleviating Poverty: An Analytical Study - Mazloum Yar, Fayaz Gul; Ihsan Ullah Nasih, (Journal of Islamic and Social Studies, 2024)
Poverty is an undesirable social phenomenon whose existence and expansion in society lead to all-around miserable consequences in the short and long term. This ominous phenomenon is condemned in all human religions and cultures, and various ways and methods have been proposed to eradicate it from society. Islam considers a life with prosperity and peace as the natural right of human beings and confronts the obstacles to the realization of this goal. Therefore, it gives teachings to its followers that, by following them, they will enjoy a life of full joy and contention, and their physical and mental health will be guaranteed. Undoubtedly, poverty is one of the biggest concerns of all human societies and economic systems. Poverty is one of the negative phenomena that pose a threat to life. Economic schools of thought have presented different ways to deal with it, but so far, they have not yet succeeded in eliminating poverty from human lives. Its occurrence is called an unpleasant complication. Poverty is one of the most important long-standing issues in developed and developing countries, including Islamic countries. To solve the problem of poverty, many studies have studied the factors affecting poverty. The purpose of this research is to identify the role of Islam in reducing poverty. In the question of the research, it is stated that what is the role of Islam in reducing poverty, and what are its recommendations for reducing poverty? The research method in this study is descriptive-analytical, and the required information was collected from library sources and a combination of the Delphi method.